In Silico Pharmacological and Pharmacokinetic Study of Marmeline From Bael Fruit for the Treatment of Alzheimer’s Disease - Tassanee Ongtanasup; Onkamon Jampa; Nattawan Suwannakul; Komgrit Eawsakul (Advances in Pharmacological and Pharmaceutical Sciences)
Epidemiological studies identify risk factors for Alzheimer’s disease (AD), which induces oxidative stress and inflammation. Pharmaceuticals aimed against the nuclear receptor PPARγ, including TZDs, have been associated with considerable negative consequences in AD treatment. The bael fruit (Aegle marmelos) has bioactive compounds with therapeutic promise. The purpose of our study was to investigate the pharmacological and pharmacokinetic properties of marmeline, a bioactive compound isolated from Aegle marmelos, as a potential therapeutic agent for AD. Specifically, we aimed to identify its molecular targets with respect to AD pathology, compare its binding affinity with important AD proteins (BACE1 and AChE) to established drugs, predict its metabolism through in silico liver metabolism studies, assess its pharmacokinetic properties, particularly blood–brain barrier permeability, determine optimal solvent conditions for extraction, and investigate gene expression patterns to understand its effects on AD. Network pharmacology investigation reveals that marmeline activates PPARγ in brain cells via the PPAR–PPRE pathway. Marmeline reduces BACE1 by higher binding affinity than donepezil and verubecestat, therefore, perhaps reducing amyloid-beta generation. Marmeline also targets increased CDK6 and PDE5A, which regulate cognition, amyloidogenesis, and neuroinflammation. Marmeline’s cognitive advantages might result from neuroinflammation control and synaptic plasticity. Using acetone helps stable marmeline extraction remain the most effective. These results suggest that by altering amyloid-beta aggregation, tau phosphorylation, and oxidative stress, marmeline could be a possible natural AD therapy, though further in vitro testing is required.